Gingival health and the effects of oral contraceptives: a literature review (Brazilian Journal of Health Research, 2024)
Introduction: Oral contraceptives (OC) contain estrogen and/or progesterone and act by inhibiting the secretion of FSH and LH and, consequently, ovulation, as well as inducing changes in cervical mucus to reduce the possibility of implantation. Circulating female hormone levels can interfere with gingival health by modulating inflammatory responses to dental plaque. Objective: To identify scientific evidence regarding the effects and impacts of continuous oral contraceptive use on periodontal health. Methods: Narrative review through a survey of original research from the BVS, PubMed, Cochrane, and SciELO databases, including studies published since 2010. Results: Ten articles were included. The most evaluated clinical parameters were Plaque Index (PI), Gingival Index (GI), Probing Depth (PD), Attachment Loss (AL), and Bleeding on Probing (BP). Users of oral contraceptives had significantly higher GI, BP, PD, and AL compared to control groups, with these parameters worsening with prolonged OC use. Conclusion: The use of oral contraceptives, even at lower doses, can negatively affect gingival and periodontal health. However, the results are still divergent, and the studies have limitations, preventing definitive conclusions.
Keywords: Oral contraceptives; Periodontium; Gingival diseases